Preliminary Reliability Allocation Method for Fusion Facility Based on Probabilistic Safety Assessment. (17th November 2019) - Wang, Dagui; Wang, Jin; Hu, Liqin; Wu, Jie; Wang, Fang
Abstract: The construction of ITER indicates that the development of fusion energy has entered the engineering stage. Reliability assurance, which is essential in the design and safety supervision of a new reactor, is an urgent problem to be solved in the process of fusion reactor engineering. But, up to now, the reliability work of a fusion device has not considered the security of the fusion reactor. This paper proposes a method to establish a reliability index for fusion safety–related components. The reliability index is a useful indicator to evaluate the reliability of the system, and it is also the regulatory basis for regulatory authorities. First, this paper gives the recommended values of probability safety goals for a fusion reactor. Second, the reliability requirements for the fusion safety system that meet the safety goals are calculated. In this part, a Probability Safety Assessment (PSA) is adopted to establish the risk models and calculate the undesired consequences of a fusion reactor. Based on the PSA analysis results, a risk-informed approach is used to categorize the plant structures, systems, and components of the fusion reactor as four categories according to their safety significance. Last, the reliability index of the safety-related components is given based on the results of the risk-informed safety categorization and PSA analysis results. The validation of the reliability index system is still being studied, and this work is expected to support the reliability evaluation and safety supervision of a fusion reactor in the future.